2015
DOI: 10.1080/08927022.2015.1067368
|View full text |Cite
|
Sign up to set email alerts
|

A DFT based assay for tailor-made terpyridine ligand–metal complexation properties

Abstract: Supp-Tab. 1: M-N Bond Lengths ( Å), Dihedral angle and N-M-N bond angles (in degrees) in Functionalized TPy-M Complexes. The Corresponding Geometrical Parameters in Unfunctionalized TPy-M Complexes are also Given for Comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It has been well documented that the Fe atom/ion shows strong coordination interaction with tpy ligand both in solution and on surfaces 49,5154 . The theoretically estimated binding energy of Fe-tpy up to ~287 kJ per mol 55 is expected to afford a good template effect, with which the conformation and the coordinative/covalent coupling mode of the (Br-)tpy entities can be selected.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well documented that the Fe atom/ion shows strong coordination interaction with tpy ligand both in solution and on surfaces 49,5154 . The theoretically estimated binding energy of Fe-tpy up to ~287 kJ per mol 55 is expected to afford a good template effect, with which the conformation and the coordinative/covalent coupling mode of the (Br-)tpy entities can be selected.…”
Section: Resultsmentioning
confidence: 99%
“…From this point of view, polypyridyl complexes, such as terpyridines, linked via transition metal ions are promising entities. However, this class of macromolecular complexes often suffers from low intrinsic quantum yields ( Q i o ) due to an effective coupling between the radiative metal-to-ligand charge transfer (MLCT) states and metal-centered states caused by their distorted octahedral geometry. Nonetheless, it has been already shown that their emission properties can be improved in terms of their room-temperature (RT) emission, their intrinsic quantum yields, extended lifetimes of their MLCT states, and their spectral properties. ,, In general, tailored photophysical properties can be accomplished by synthetic routes, i.e., by the insertion of electron-donating or -accepting functional groups, in order to control the electronic coupling of the ππ* excited state and the simultaneously present MLCT states. ,, Alternatively, the insertion of heterocyclic groups can change the torsion angle between the terpyridine cage and the ligand, leading to a less distorted planar ground-state configuration. , Key for the improvement of their photophysical properties with respect to an application in photovoltaics or light-emitting devices is an extension of the electron delocalization and the minimization of nonradiative relaxation channels. In order to improve the applicability of these coordination compounds in optoelectronic devices, a detailed knowledge of their homogeneity and environmentally influenced alteration of their luminescent properties is indispensable.…”
mentioning
confidence: 99%